Burocracia e custo de transação econômica: um estudo de caso nos projetos de extensão da universidade federal rural do semi-árido (ufersa) - Oliveira, Oskarine da Chagas (Universidade Federal Rural do Semi-Árido, 2019)
This paper has the objective of identifying the effects of bureaucracy in the cost of economic transacions in the extension projects with external funding at Universidade Federal Rural do Semi-Árido (UFERSA). For that purpose, a qualitative method research, as well as an exploratory and descriptive survey plan were used. For the development of this paper, a case study was applied at UFERSA, in which a triangulation of data was employed by using observation, interviews and data analysis. Concurrently, semi-structured interviews were conducted with the personnel responsible for the process, celebration and execution of those externally funded extension projects. The participants of the research were: The Division of Projects (DDP), the Dean of Culture and Extension (PROEC), the Division of Contracts (DICONV), the Dean of Planning (PROPLAN), the Guimarães Duque Foundation; a group that acts as technical and operational support in the execution of the projects and three extension project coordinators. The data gathered was analysed, at first by transcribing the material from the interviews and furthermore imported to software Atlas ti 8.4. The coding work was then made and after that was finished, the categorization of data was employed with the purpose of creating family trees acording to the dimentions studied. After that, it was possible to conceive networks for the necessary analysis and discussions. The results gathered show evidences that the rules and regulations that control the relations of the subjects in this paper attenuate the effects of limited racionality, uncertainty and opportunism. However, it was noted that the excessive use of rules and regulations created bureaucratic disfunctions and generated transaction costs between the subjects. Therefore, this paper contributes to the evidences that the use of bureaucracy, more precisely, it‟s disfunction, causes problems in the relation of subjects that work in the processing of the extension projects and also emphasizes the cost increase in economic transactions
Keywords: Burocracia; Custo de transação; Projetos de extensão; Bureaucracy; Transaction costs; Extension projects; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA